Profile of patients with bucket handle injury at Dr. Soetomo General Hospital Surabaya from 2020 to 2024 - Putra, Ida Bagus Trisnanda; Danardono, Edwin; Septarendra, Denny (Edelweiss Applied Science and Technology, 2025)
Bucket handle injury tear is a traumatic injury to the abdomen where mesenteric avulsion of a segment of the intestinal loop occurs, potentially resulting in devascularization, ischemia, and hollow organ perforation. A prior systematic review reported 20 cases of mesenteric avulsion after blunt abdominal trauma and found that only 25% of cases exhibited symptoms of shock and/or hemodynamic instability. The objective of this study is to describe the profile of patients with bucket handle injury at Dr. Soetomo General Hospital, Surabaya, from 2020 to 2024. This study is descriptive research with a retrospective study design. Data will be collected from the medical records of patients treated at Dr. Soetomo General Hospital during the 2020–2024 period. Various parts of the intestine were affected, with the ileum being the most commonly involved in 10 patients (50%). Trauma to the transverse colon was observed in 5 patients (25%), the sigmoid colon in 4 patients (20%), and the jejunum in 1 patient (5%). The most commonly performed procedure was resection and stoma, carried out in 11 patients (55%). This was followed by damage control surgery in 3 patients (15%), resection and EEA in 2 patients (10%), Hartmann’s sigmoidectomy in 2 patients (10%), and other procedures in 2 patients (10%). After treatment, 11 patients survived (55%), while 9 patients passed away (45%). A common location for bowel wall hematoma (BHMT) in blunt abdominal trauma is near the junction of fixed and mobile bowel segments, such as the proximal jejunum and distal ileum.